Oil price changes and stock returns: Fresh evidence from oil exporting and oil importing countries - Mohd Atif; Mustafa Raza Rabbani; Hana Bawazir; Iqbal Thonse Hawaldar; Daouia Chebab; Sitara Karim; Amani AlAbbas (Cogent Economics & Finance, 2022)
The study examines the vital connection between stock returns and oil price changes for oil exporting/importing countries separately. We present evidence employing granger causality, impulse response and error variance decomposition based on panel vector autoregression. The results of panel granger causality suggested that after oil price crash owing to covid-19 pandemic, the interdependence between oil and stock price changes increased. Similar results were revealed by impulse response graphs and forecast error variance decomposition. Specifically, in the period marked by the rapid outbreak of the covid-19 pandemic, causality from oil to stocks increased. Although we found that both oil exporting and oil importing countries were affected in a similar way, oil price changes had a larger impact on oil exporting countries. The findings of the present study have implications for investors and fund managers. By incorporating crude oil price in the prediction models, the accuracy of stock returns forecast can be improved.
Keywords: G30; G32; G11; 330; Covid-19; panel granger causality; oil price; panel vector autoregression; stock returns